A study on customer relationship marketing as practised by the Konsortium Peladang Terengganu Sdn.Bhd ( KPT Peladang Sdn.Bhd) / Zakaria Abdullah - Abdullah, Zakaria (2007)
KPT Peladang Sdn.Bhd was incorporated on April 1995 and commence operation on the 1st Jan 1996 with authorized capital of RM 1,000,000 and paid up capital of RM 500,000. The incorporation of KPT Peladang Sdn.Bhd was based on several meeting and brainstorming sessions held among the officers of Terengganu Farmers Organization Authority